Mortalitas Penggerek Ubi Jalar (Cylas formicarius) Akibat Aplikasi Cendawan Entomopatogen Beauveria bassiana dan Insektisida Nabati Ekstrak Daun Pepaya (Carica papaya L.) - Syaswina Azzahra; Lutfi Afifah; Tatang Surjana (Universitas Respati Indonesia, 2026)
Cylas formicarius is a major pest of sweet potato plants in Indonesia that can disrupt and harm farmers because this pest can reduce sweet potato yields by up to 100%. Beauveria bassiana is an entomopathogenic fungus that has the potential to be a plant pest control agent. Papaya leaves are one of the plants that have the potential to control pests. This study aims to obtain effective treatment increasing mortality and suppressing the attack of Cylas formicarius. The method used was an experimental method with a single-factor Completely Randomized Design (CRD) consisting of 7 treatments and 4 replications: A (Control aquadest); B (40% Papaya leaf extract); C (60% Papaya leaf extract); D (80% Papaya leaf extract); E (Beauveria bassiana 109 + 40% Papaya leaf extract); F (Beauveria bassiana 109 + 60% Papaya leaf extract); G (Beauveria bassiana 109 + 80% Papaya leaf extract). Data were analyzed using F-test and Duncan Multiple Range Test (DMRT) at a 5% significance level. The results showed that the treatment G (Beauveria bassiana 109 + 80% Papaya leaf extract) achieved the highest mortality of 100%. Treatment F (Beauveria bassiana 109 + 60% Papaya leaf extract) gave an average mortality result of 82,50%. The best average LC50 concentration was 63,40%. Thus, treatment F (B. bassiana 109 + 60% Papaya leaf extract) is more recommended to controlling and suppressing the population Cylas formicarius as it requires less raw material and so it is more efficient